Experimental investigation of the vortical flow around a reverse delta wing using PIV - Altaf, Afaq; Omar, Ashraf Ali E.; Asrar, Waqar (2010)
Particle Image Velocimetry was used in a low speed wind tunnel to investigate the vortex structures of a slender reverse delta wing at various angles of attack and roll. This work investigates the characteristics of the vortices generated downstream in a plane perpendicular to the free stream direction and their dependence on angles of attack and roll angles at chord based Reynolds number.